PKM UPAYA PENINGKATAN KEMPAUAN BTQ USIA ANAK 3 SAMPAI DENGAN 11 TAHUN MENGGUNAKAN FLASH CARD - Mhd Yusuf1, Lili Herawati Parapat2, Rahmat Huda3, Irmadani Parapat4, Hanifah Parapat5 (PAKAT: Jurnal Pengabdian Kepada Masyarakat, 2024)
Efforts to improve BTQ abilities of children aged 3 to 11 years using flash cards will improve children's ability to pronounce letters and know them well. This activity will be divided into 3 sessions: a) reading b) writing session, c) and playing using flash cards. Priority training and special assistance for children aged 3 years to 4 years at RCM Gunung Teletabis Housing Block D. No. 11 Batunadua Padangsidimpuan. Based on the results of the implementation of community service in improving children's abilities, this PKM has carried out coaching to Read and Write the Qur'an properly with the children at the RCM Gunung Teletabis Housing Block D. No. 11 Batunadua Padangsidimpuan. Has made a video documentation of Community Service. Through the use of Flash card learning media, children aged 3 years have known hijaiyah letters for ± 1 month. Children aged 4 to 11 years are more fluent in pronouncing hijaiyah letters. Documentation of activity implementation.